Analisis Pengaruh Citra Rumah Sakit Dan Kualitas Pelayanan Terhadap Kepuasan Pasien Di Instalasi Rawat Inap Rumah Sakit Umum Daerah (RSUD) Kota Tangerang - Dewi Winarsih; Eddy Hermawan Hasudungan Panjaitan; Nurwulan Kusuma Devi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Hospitals as public service institutions are required to provide services that are available, continuous, acceptable, easily accessible, affordable, and of quality. Hospital image and service quality as a liaison and guardian of relationships with customers to maintain patient satisfaction. This study is to analyze the influence of hospital image and service quality simultaneously on inpatient satisfaction at Tangerang City Hospital. The research method uses a quantitative cross-sectional approach with a saturated technique sample (84 respondents). Data were collected through questionnaires and analyzed using the interval analysis method. The results show that there is a significant influence between hospital image and service quality on patient satisfaction (T sig test = 0.000 <0.05; F sig test = 0.000). The conclusion and suggestion of the researcher is that the variables of hospital image and service quality together can provide a positive and significant influence on patient satisfaction at Tangerang City Hospital and management support, technical services both medical and non-medical, communication staff, and infrastructure facilities to strengthen patient satisfaction.